Hydrogen bonding phase-transfer catalysis with alkali metal fluorides: enantioselective synthesis of β-fluoroamines from reaction development to scale-up - Vicini, AC (2020)
This thesis reports the development of hydrogen bonding phase-transfer catalysis (HB PTC) for asymmetric fluorination with alkali metal fluorides. This catalytic manifold harnesses the ability of fluoride to engage in hydrogen bonding to promote solubilisation of the inorganic fluoride salt, with concomitant formation of a reactive chiral catalyst fluoride complex. Herein, HB-PTC has been applied to the synthesis of enantioenriched β fluoroamines, with a focus on the industrial application of the methodology.